Comparison of obese and non-obese patients in terms of sharp object injuries: A retrospective evaluation - Talih, Tutkun; Topal, Ugur; Mutevelli Sozuer, Erdogan; Dal, Fatih; Yakup Akyildiz, Hizir (Annals of Medical Research, 2021)
Aim: In our study, we aimed to investigate the effect of BMI on surgical treatments and general outcomes, as well as on the severity of the injury caused by the sharp object. From an anatomical point of view, increased body mass index (BMI) is expected to have a protective effect in limiting organ damage in the case of sharp object injuries. Material and Methods: Data of the patients with penetrating abdominal injuries who applied to the emergency service of the University between January 2015 and January 2020 were analyzed retrospectively. Patients’ ages, genders, body mass indexes (BMIs), needs for surgical intervention, injury severity scores (ISS) and mortality were evaluated. Patients were divided into 2 groups: obese patients (BMI>30; Group1) and non-obese patients (BMI30; Group2). Results: Seventy-eight patients whose data were available were included in the study. Thirty-three of the patients were determined to be obese (Group1) while 45 were determined to be non-obese (Group2). The mean age of the patients in group1 was significantly higher than the patients in group 2 (p=0.011). The mean ISS of the patients in group 1 was 11.03±8.24 while it was 16.93±13.68 in group 2. The ISS was significantly higher in group2 (p=0.031). Alcohol intoxication levels of the patients in Group 2 were significantly higher than Group 1 (p=0.006). A statistically significant difference was not present between the groups in terms of number of past surgical interventions (p=0.627); however, it was determined that 57% of the surgical interventions in Group 1 were performed for diagnostic purposes and that no pathologies were detected in 45% thereof. Discussion: As a result, increased BMI is associated with lower injury severity scores and decreased need for operation in sharp object injuries. Slim patients are more likely to need surgery and be severely injured.